2002
DOI: 10.1080/00207720210133598
|View full text |Cite
|
Sign up to set email alerts
|

Open hypermedia for product support

Abstract: As industrial systems become increasingly more complex, the maintenance and operating information increases both in volume and complexity. With the current pressures on manufacturing , the management of information resources has become a critical issue. In particular, ensuring that personnel can access current information quickly and e ectively when undertaking a speci®c task. This paper discusses some of the issues involved in, and the bene®ts of using, open hypermedia to manage and deliver a diverse range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Nevertheless, it is found that business benefit can be derived from hypermedia-based systems, due to substantially lower administrative costs than than those incurred with paper-based systems (Wills et al, 2002). Provisional cost-benefit analysis estimates an annual saving of £50,000 and a 3-year payback on investment at the evaluation research setting.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Nevertheless, it is found that business benefit can be derived from hypermedia-based systems, due to substantially lower administrative costs than than those incurred with paper-based systems (Wills et al, 2002). Provisional cost-benefit analysis estimates an annual saving of £50,000 and a 3-year payback on investment at the evaluation research setting.…”
Section: Discussionmentioning
confidence: 98%
“…The application of kiosks in manufacturing could therefore be appropriate to add security and robustness to hypermedia-based systems. Wills, Sim, Crowder, and Hall (2002) find that accurate retrieval of required information within a manufacturing system is considered time critical. Conventional information management techniques are found to be insufficient due to the high number of documents requiring cross-referencing in a variety of formats (Wills et al, 2002).…”
Section: Information Kiosksmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the increase in virtual enterprises, lean and agile manufacturing, the demands for correct and easily accessible information have not abated. Wills et al have demonstrated the effective application of open hypermedia to industrial applications [22].…”
Section: Introductionmentioning
confidence: 99%